1994
DOI: 10.1017/s0960258500002142
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soluble sugars in relation to desiccation tolerance in cauliflower seeds

Abstract: Changes in soluble sugars in cauliflower seeds were followed during 50 h of imbibition in relation to desiccation tolerance Sucrose and stachyose contents decreased, and glucose and fructose accumulated This occurred in radicles first and subsequently in hypocotyls and cotyledons Loss of desiccation tolerance in the various seed parts coincided with an increase in glucose and fructose and the complete loss of stachyose, but sucrose content, the major sugar, was still high Drying imbibed seeds over silica gel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…Nevertheless, a considerable percentage (74%) of the 25-DAP embryos survived rapid drying, in spite of the fact that raffinose was almost absent. Therefore, raffinose is not a prerequisite for desiccation tolerance, as was stipulated earlier for immature maize embryos (Bochicchio et al, 1994b) and primed cauliflower seeds (Hoekstra et al, 1994). As expected, membrane permeability of the rehydrated, 25-DAP, rapidly dried embryos was much lower than that of the rapidly dried, 20-DAP embryos.…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, a considerable percentage (74%) of the 25-DAP embryos survived rapid drying, in spite of the fact that raffinose was almost absent. Therefore, raffinose is not a prerequisite for desiccation tolerance, as was stipulated earlier for immature maize embryos (Bochicchio et al, 1994b) and primed cauliflower seeds (Hoekstra et al, 1994). As expected, membrane permeability of the rehydrated, 25-DAP, rapidly dried embryos was much lower than that of the rapidly dried, 20-DAP embryos.…”
Section: Discussionsupporting
confidence: 67%
“…Soluble sugars of isolated axes were extracted in a solution of 80% methanol (v:v) containing lactose as internal standard according to Hoekstra et al (1994). Sugar concentrations were determined by HPLC using pulsed amperometric detection on a Carbopac PA-1 column (Dionex Corp., Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The causes for this reduced longevity are not well understood. Hoekstra et al (1994) found that priming of cauliflower seeds resulted in a decrease in oligosaccharide content. Considering the proposed role of oligosaccharides in increasing glass stability, it is possible that the reduced longevity of primed seeds may be attributed to the decrease in oligosaccharide content resulting in a decrease in cytoplasmic viscosity.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations